Short-term intradialytic NMES targeting muscles of the legs improves the phase angle: A pilot randomized clinical trial - Marini, Ana Clara B.; Motobu, Reika D.; Freitas, Ana Tvs; Mota, Joao F.; Monteiro, Paula A. [UNESP]; Pichard, Claude; Laviano, Alessandro; Wall, Benjamin T.; Pimentel, Gustavo D. (Elsevier B.V., 2021)
Purpose: Neuromuscular electrical stimulation (NMES) elicits muscle contraction and has been shown to attenuate muscle atrophy when physical activity is not possible. Thus, we hypothesized that intradialytic NMES would attenuate the loss leg lean mass and improve the phase angle in patients undergoing hemodialysis (HD). Methods: A randomized controlled trial was performed with twenty-one adult HD patients (n = 8 F, n = 13 M; 45.8 +/- 10.6 y) randomly assigned to usual care (control group, n = 11; 4F/7M) or to the NMES group (n = 10; 4F/6M). NMES was applied bilaterally at the origin and insertion points of the quadriceps or gastrocnemius muscles for 40 min during each HD session (3x/wk for one month). Pre-and post-intervention, we measured leg lean mass using dual-energy x-ray absorptiometry and phase angle using bioelectrical impedance analysis. Results: NMES did not change leg lean mass compared to the control group. Phase angle increased in the NMES compared to the control group (Delta: +0.71 +/- 0.27 degrees vs. -0.46 +/- 0.23 degrees, p = 0.004) with interaction time x treatment (ANOVA p = 0.004). Conclusion: Short-term intradialytic NMES targeting muscles of the legs improved the phase angle but did not change leg lean mass. Brazilian registry of clinical trials under the code: RBR-98wzgn. (C) 2021 European Society for Clinical Nutrition and Metabolism. Published by Elsevier Ltd. All rights reserved.
Keywords: Hemodialysis; Phase angle; NMES; Lean body mass